Estimativa de indicadores biofísicos para avaliação do processo de desertificação no município de São João do Cariri- PB - Silva, Glauciene Justino Ferreira da (2014)
The degradation of the semiarid lands in Northeast region of Brazil is increasing, thus favoring the lost of its typical vegetation called Caatinga it is provoking the exhaustion of the soils, water resources and also spreading the process of soil desertification. The semiarid lands in Paraiba state are very heterogeneous in the socio-environmental point of view. Than it is necessary an urgent planning to solve those problems. The understanding of the different landscapes in this region and the obtaining of data from the bio-climate aspects, in fact, is an alternative to understand the dynamics of degradation of the lands and its consequent desertification. In this context the use of remote sensing data has giving information to the biophysical variables involved in the environmental equilibrium by the balance of radiation. In this way, this research has as a goal to demonstrate the biophysical indicators potentials to evaluate the process of desertification and its consequent alterations in the landscape of the experimental basin in São João do Cariri, located in the microregion of Cariri in Paraiba state. With the use of the techniques of remote sensing, field research and the use of the SEBAL algorithm it was possible to analyze many biophysical indicators, such as albedo, vegetation indices (IAF, NDVI and SAVI), the land surface temperature, net radiation and the soil heat flux. The results obtained show that the area studied has already presented higher levels of degradation, what makes almost impossible the development of the vegetation. The natural potential of erosion (NPE) displayed that the area presents high loses of soil. Its erosion is getting 135 ton a year. With the spatial distribution of the variables, we concluded that the values founded were consistent in relation to the consulted literature to the area of Caatinga. The albedo of the surface presented high values in the area of exposed soil and its special variation was consistent with its location. The SAVI presented values more consistent with the vegetal diversity founded in the area, when compared with NDVI. The IAF presented higher values for the Caatinga area, between (0 6), which could display a major density of vegetal bio-mass in the area of study. However, the low diversity founded in these areas shows that the higher values were obtained for the exotic vegetation. The spatial distribution of the land surface temperature ranged according to the presence of vegetation that even thin and spaced decreased the soil temperature and protected it from the erosive action provoked by the impact of the intense and irregular rains. It was checked that the low values of net radiation (Rn) were presented in the most degraded areas of the basin (west portion). These were also the areas with higher values of the soil heat. The estimated values were mainly by the land covers and reflected the level of degradation of the basin.